Analyzing Students’ Critical Thinking Ability on Solving Sequences and Series Problems through Problem-Based Learning with Islamic Nuance - Tri Utami, Yudy; ., Susanto; Irvan, Muhtadi (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed to analyse the ability of critical thinking to solve sequences and series problem through Problem-based Learning (PBL) with Islamic Nuance. Research instruments operative included instructional instruments (lesson plan and students’ work sheet); learning achievement test, questionnaire; critical thinking assessment sheet, and documentation. The lesson plan and students’ work sheet validation results evinced values of 3.73 and 3.74. The research generated the data concerning students’ activity during instructional process from the first to third meeting respectively as follows; 60%, which meant good category, 80%, indicating very good category, and 83.33%, evincing very good category. The minimum criterion of learning achievement was achieved because more than 80% of students gained score of at least 60, that was 27 students (90%) passed and 3 students (10%) below passing criteria. From the data analysis, it found that students' critical thinking ability in solving Sequences and Series problem through PBL was very satisfactory.